Application Status of Coal Series Kaolin in China - Man Chen; Xiaoting Chen; Teng Huang; Chunlong Luo; Caipeng Liu; Meng Li (Kuangchan zonghe liyong, 2022)
Coal Series Kaolinite (CK) is the industrial solid waste produced in coal mining and processing. CK is an indispensable raw material for new ceramics, high-end paper and advanced coatings, attribute to its advantages of pure soil quality, good wear resistance and high whiteness. China is a major kaolin producer, the coal-series kaolin reserves rank first in the world, and we need to pay attention to and solve how to effectively research and use these resources. Therefore, the introduction, main distribution, common application, main processing technology and development trend of CK are summarized. Through the comprehensive and detailed introduction, the innovative research and application of CK will be promoted.